Implementasi Program "Malware" pada Smartphone untuk Meningkatkan Literasi Digital pada Masyarakat Kendalpecabean Candi Sidoarjo: Implementasi Program "Malware" pada Smartphone - Rafi Nashirudin; Arina Farikhatul Lutfita; Shavira Nur Innayah; Aminatuz Zuhroh; Ika Fitrianingsih; Annisa Rosheila Rahma Habiba (Journal of Science and Social Development, 2022)
Android is the most widely used mobile operating system today. This is what makes it the most widely used mobile operating system even surpassing the Windows operating system. However, the popularity of Android does not always have a positive impact on its users. One of the negative impacts is the problem the most populous malware on the Android operating system. The Android system is the main target for mobile malware because the Android operating system allows users to install applications downloaded from third-party marketplaces.Malware stands for English term malicious software, which means suspicious software is a computer program that was created with the intent and purpose of its creator and is a program that looks for weaknesses in software. Generally, malware is created to break into or damage a software or operating system through a script that is inserted regularly hidden by the creator. This malware can secretly make the victim's cellphone subscribe to pay premium services without the victim's knowledge. mobile devices connected to the internet, and exploiting other cellular phones that are connected to the internet. The existence of security holes in the operating system causes weaknesses and opens loopholes that can be used by hackers to infiltrate the system of mobile devices. Cybercrime is better known as cyber crime. Cybercrime is a form of crime that should not be committed by everyone. Cybercrime is a crime that is committed in cyberspace through computers or the internet. Cybercrime is included in the category of criminal acts of crime. use technology.